2016
DOI: 10.1016/j.aogh.2016.04.405
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of health services in a resource-limited rural area in Kenya: prevalence and associated household-level factors

Abstract: Background and methods

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 8 publications
2
9
0
Order By: Relevance
“…Our results emphasize cost as the major reason for not seeking healthcare at 38.6%. This is in accordance with other studies in Kenya, and elsewhere that highlight cost as an important and most frequent reason for unmet need for care [25,[44][45][46]. The findings slightly differ from those of the national report because we define cost-related unmet need as a combination of two reasons "lacked money" and "high costs of care", whereas the national report focused on only the high cost of care.…”
Section: Discussionsupporting
confidence: 84%
“…Our results emphasize cost as the major reason for not seeking healthcare at 38.6%. This is in accordance with other studies in Kenya, and elsewhere that highlight cost as an important and most frequent reason for unmet need for care [25,[44][45][46]. The findings slightly differ from those of the national report because we define cost-related unmet need as a combination of two reasons "lacked money" and "high costs of care", whereas the national report focused on only the high cost of care.…”
Section: Discussionsupporting
confidence: 84%
“…This might be this study only in urban residents only because urban residents have access to the health facility. It is comparable to a study done in Kenya (10). Half of them were rst to visit primarily at the public health center and 25.5% of them were at Teaching and Referral Hospital.…”
Section: Discussionsupporting
confidence: 83%
“…For instance, a study in Tanzania found that despite the vast majority of the population live within 5 km of a health facility, only 40-54% of caretakers with febrile children seek healthcare [75]. Studies in Kenya reported that 76.7%-87.3% of the population sought treatment from healthcare service providers [76,77]. Like in Tanzania, relatively lower prevalence rates among rural populations of Uganda (54.1%) [78], Zambia (56.8%), [79], Ghana (55.5%) [80] and Ethiopia (43.2%) [81] seek care from conventional healthcare facilities.…”
Section: Performance Of Idsr Strategymentioning
confidence: 99%